Free vibration analysis of a newly developed 8-node quadrilateral element (USQUAD8) - Jway, Jermain Jiang Yuan (2019)
The classical 8-node iso-parametric element uses parametric shape functions for its formulation. This classical element provides consistent and accurate results in general., However in the presence of mesh distortion, it yields poor results. It is well-known that this is due to the lack of completeness of shape functions. A recent study shows that a new element that uses both parametric and metric shape functions exhibits excellent mesh distortion immunity. This has been demonstrated for static analysis and not yet for vibration analysis, and hence this project aims to investigate how this element performs for free vibration analysis. The natural frequencies of four versions of 8-node element elements, viz., parametric, metric, parametric-metric and metric-parametric, are determined for typical distorted meshes in order to determine how well the new element performs as compared to others under extreme mesh distortions.